Acoustic comfort in industrial office: A preliminary study at a manufacturing company in Malaysia - Selamat F.E.; Zulkifli R. (Malaysian Public Health Physicians Association, 2023)
Acoustics issues such as noise in the workplace remains one of the most prevalence occupational hazard especially in the manufacturing industry with heavy machineries. Increasing mechanization in all industries and most trades has since proliferated the noise problem. In Malaysia, much has been studied and is known about the auditory effects of noise. However less attention has been given to the non-auditory effects of noise such as annoyance, stress, and work performance, and concern about such effects is a relatively recent phenomenon. In view of this, this study aims to determine the level of noise from different type of machines and tools in a manufacturing plant and also the effects of noise to the employees. A structured questionnaire was used to assess the effects of noise on the workers and sound level meter was used to measure the noise level at selected work areas. The results of this study showed that nearly all the identified work areas exceeded the action level of 85 dB(A) and four of these areas noise levels' are more than 90 dB(A) which is the permissible exposure limit according to the Factories and Machinery (Noise Exposure) Regulations 1989. For the questionnaire, it was found that annoyance topped the noise effects list with 51.4%, followed by stress with 40.0%, hearing deterioration (14.3%) and job performance deterioration (2.9%). As a conclusion, noise control or preventive measures are suggested in order to minimize the health risks from noise exposure.